2022
DOI: 10.1093/mnras/stac3369
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing the star formation quenching in L* ellipticals

Abstract: We study the evolution of L* elliptical galaxies in the color-magnitude diagram in terms of their star-formation history and environment, in an attempt to learn about their quenching process. We have visually extracted 1109 L* galaxies from a sample of 36500 galaxies that were spectroscopically selected from Stripe82 of the Sloan Digital Sky Survey. From this sample we have selected 51 ellipticals based on their surface-brightness profile being well-fitted by a single S$\acute{e}$rsic profile with S$\acute{e}$… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…This is supported by the higher fraction of blue ETGs for A3560, which, despite showing characteristics of relaxed clusters, is part of the broader Shapley Supercluster system and hence connected with the cosmic web network. Furthermore, Dhiwar et al (2023) find that blue ETGs with Milky Way-like stellar masses (logM * /M ∼ 10) reside in low-density environments, making them a probable population of the cosmic filament-like environment now observed as a part of the newly forming post-merger system. Despite lacking specific stellar population information for these galaxies, our forthcoming follow-up work (Kelkar et al, in prep.…”
Section: Blue Etgs In Merging Clustersmentioning
confidence: 97%
“…This is supported by the higher fraction of blue ETGs for A3560, which, despite showing characteristics of relaxed clusters, is part of the broader Shapley Supercluster system and hence connected with the cosmic web network. Furthermore, Dhiwar et al (2023) find that blue ETGs with Milky Way-like stellar masses (logM * /M ∼ 10) reside in low-density environments, making them a probable population of the cosmic filament-like environment now observed as a part of the newly forming post-merger system. Despite lacking specific stellar population information for these galaxies, our forthcoming follow-up work (Kelkar et al, in prep.…”
Section: Blue Etgs In Merging Clustersmentioning
confidence: 97%
“…A popular way to categorize galaxies is via the D n 4000-Hδ plane (e.g., Kauffmann et al 2003;Borgne et al 2006;Kauffmann 2014;Maltby et al 2016;Wu et al 2018;Dhiwar et al 2023). To investigate how different types of galaxy populations are located in the D n 4000-Hδ plane, we also include model quiescent and post-starburst populations here for comparison purposes.…”
Section: Hδ Versus D N 4000mentioning
confidence: 99%
“…Wild et al (2016) also used photometric data (using a supercolor selection) to identify post-starbursts and concluded that the post-starburst phase accounts for 25%-50% of the growth of the red sequence at z ∼ 1. In summary, quite a significant fraction of quiescent galaxies can be explained by the PSB phase (e.g., Snyder et al 2011;Wild et al 2016;Dhiwar et al 2023), especially at higher redshifts, highlighting the importance of the rapid quenching phase.…”
Section: Introductionmentioning
confidence: 96%